CONCEPTUAL BASIS OF FINANCIAL REPORTING - Kholmatov Dyorbek Usmonovich. (Western European Studies, 2024)
this article describes the procedure for preparing and submitting financial statements in accordance with International Financial Reporting Standards and its conceptual issues. It contains scientific recommendations on the preparation of financial statements on the basis of IFRS (International Accounting Standard, IAS) and its purpose in ensuring the implementation of the Resolution of the President of the Republic of Uzbekistan No. PQ-4611.
Keywords: concept; financial reporting; period; balance